Tratamiento de residuos líquidos mineros , aplicando peróxido de hidrógeno en la empresa minera Franromec. - Ortiz Mejia, Betsy Beatriz (2015)
For gold recovery it is applied the cyanide leaching process, which being a highly toxic compound has proposed its elimination in our country.